Somatic Embryogenesis Induction in Woody Species: The Future After OMICs Data Assessment - Pais, Maria Salomé (Frontiers in Plant Science, 2019)
Very early somatic embryogenesis has been recognised as a powerful method to propagate plants in vitro. For some woody species and in particular for some coniferous trees, somatic embryogenesis induction became routine procedures. For the majority, the application of this technology presents yet many limitations especially due to the genotype, the induction conditions, the number of embryos produced, maturation and conversion, among other factors that compromise the systematic use of somatic embryogensis for commercial purposes especially of woody species and forest trees in particular. The advancements obtained on somatic embryogenesis in Arabidopsis and the development of OMIC’s technologies allowed the characterization of genes and the corresponding proteins that are conserved in woody species. This knowledge will help in understanding the molecular mechanisms underlying the complex regulatory networks that control somatic embryogenesis in woody plants. In this revision we report on developments of OMIC’s (genomics, transcriptomics, metabolomics and proteomics) applied to somatic embryogenesis induction and its contribution for understanding the change of fate giving rise to the expression of somatic embryogenesis competence.